Extraction of d-limonene from pomelo (Citrus maxima) peel waste using solvent-free microwave process and antioxidant activity analysis - Chutvirasakul, Boonta; Riangnam, Thanapat; Kunkamphon, Wancharoen; Ramakul, Prakorn (Science, Engineering and Health Studies, 2025)
Solvent-free microwave assisted extraction has been performed as an efficient green technology for the extraction of d-limonene from pomelo peel waste. This environmentally friendly method does not require solvents or water and can be operated at atmospheric pressure and room temperature. The extraction results were identified by gas chromatography–mass spectrometry (GC-MS). It was found that d-limonene was the most abundant compound in the extracted essential oils, comprising 95% of the total, with an additional 17 compounds detected. For 100 grams of pomelo peel, the energy requirement was 336.0 kJ to achieve the highest yield of 1.2% essential oil by weight of the pomelo peel plant material. The essential oil showed the antioxidant activities of IC50 at 4.87 + 0.06 mg/mL using ABTS radical scavenging assay.